Lived Experiences and Perceptions of University Female Students - Kaini, Tika Raj; Dhakal, Naba Raj (Bhairahawa Campus Journal, 2023)
With the onset of modernization, intellectual women in urban areas are not extremely compelled to follow menstrual pollution. However, practices such as forbidding women from entering the temples and kitchen, cooking food, touching male members of the family, and sleeping on their usual beds when menstruating. This study aims to analyze the lived experiences of urban intellectual women during menstrual restrictions. It also discusses the perceptions of them about the tradition of menstrual restrictions. The participants are the female students pursuing their Masters’ degree in sociology at Bharaihawa Multiple Campus Rupandehi. 16 out of 42 participants were selected for interview applying purposive sampling method. The samples include the students permanently living in Bhairahawa’s city area. Semi-structured interview was applied to collect the data to discuss about what the female students experience and perceive the tradition of menstruation restrictions. Most of the participants responded that the experience of restriction is the example of structural inequality imposed upon women due to patriarchal perspective of history. They have the experiences of pain and suffering at periods. The participants responded that menstruating restriction is the practice of imposing discrimination and superiority of males. But it was also found that males’ perspective is slightly changing with the process of modernization. This research article concludes with the perception of women that menstruation practice is the stigma for the modern society today.